Roles of Parathyroid Hormone (PTH) Receptor and Reactive Oxygen Species in Hyperlipidemia-Induced PTH(1-34) Resistance in Preosteoblasts. - Li, Xin (2014)
Bioactive lipids initiate inflammatory reactions leading to pathogenesis of atherosclerosis. Evidence shows that they also contribute to bone loss by inhibiting parathyroid hormone receptor (PTH1R) expression and differentiation of osteoblasts. We previously demonstrated that bone anabolic effects of PTH(1-34) are blunted in hyperlipidemic mice and that these PTH effects are restored by antioxidants. However, it is not clear which osteoblastic cell developmental stage is targeted by bioactive lipids. To investigate the effects of hyperlipidemia at the cellular level, hyperlipidemic Ldlr(−/−) mice were bred with Col3.6GFPtpz mice, in which preosteoblasts/osteoblasts carry a topaz fluorescent label, and with Col2.3GFPcyan mice, in which more mature osteoblasts/osteocytes carry a cyan fluorescent label. Histological analyses of trabecular bone surfaces in femoral as well as calvarial bones showed that intermittent PTH(1-34) increased fluorescence intensity in WT-Tpz mice, but not in Tpz-Ldlr(−/−) mice. In contrast, PTH(1-34) did not alter fluorescence intensity in femoral cortical envelopes of either WT-Cyan or Ldlr(−/−)-Cyan mice. To test the mechanism of PTH1R downregulation, preosteoblastic MC3T3-E1 cells were treated with bioactive lipids and the antioxidant Trolox. Results showed that inhibitory effects of PTH1R levels by bioactive lipids were rescued by pretreatment with Trolox. The inhibitory effects on expression of PTH1R as well as on PTH-induced osteoblastic genes were mimicked by xanthine/xanthine oxidase, a known generator of reactive oxygen species. These findings suggest an important role of preosteoblasts as the target development stage and downregulation of PTH receptor expression mediated by intracellular oxidant stress as a mechanism in hyperlipidemia-induced PTH resistance.